Cephalometric Study of Iraqi Adult Subjects with Cl I and Cl III Skeletal Relationships and Their Effects on Masseter Muscle Thickness by Using Ultrasonography - Berum, Hibah ER; Fatah, Ahlam A (Journal of Baghdad College of Dentistry, 2016)
Background: Masseter muscle is one of the most obvious muscles of mastication and considered as one indicator of jaw muscle activity. It has a major influence on the transverse growth of the midface and the vertical growth of the mandible. This study undertaken to determine the role of cephalometric analysis for discrimination between Cl I and Cl III skeletal relationships, determine the role of ultrasonography in determination of masseter muscle thickness, compare masseter muscle thickness between Cl I and Cl III skeletal relationships, and determine the effect of gender on masseter muscle thickness.Material and Method: The sample of the current study consisted of 70 Iraqi subjects 40 males and 30 females with age ranging 18-25 years. They were divided into 2 groups depending on ANB angle: class I skeletal relationship 20 males and 15 females and class III skeletal relationship 20 males and 15 females. The collected sample included patients attended for different diagnostic purposes to the Dental Radiology Department at College of Dentistry/Babylon University, standardized lateral cephalogram was taken to determine facial morphology, six angular and eight linear measurements were assessed. Masseter muscle thickness measured ultrasonography in Al-Hilla General Teaching Hospital/Ultrasonorgaphic Department, in relaxation and contraction conditions for both sides. Results: Various parameters measured for males and females in each class and the comparison shown statistically significant differences between them (P0.05). Gender variation showed significant difference in masseter muscle thickness during rest and occlusion conditions (P